Self-microemulsifying drug delivery system (SMEDDS) for improved oral delivery and photostability of methotrexate - Kim DS (Dove Medical Press, 2019)
Dong Shik Kim1,*, Jung Hyun Cho1,*, Jong Hyuck Park,1 Jung Suk Kim,1 Eon Soo Song,2 Jaewook Kwon,2 Bhupendra Raj Giri,2 Sung Giu Jin,3 Kyeong Soo Kim,4 Han-Gon Choi,1 Dong Wuk Kim21College of Pharmacy & Institute of Pharmaceutical Science and Technology, Hanyang University, Ansan, South Korea; 2College of Pharmacy & Research Institute of Pharmaceutical Sciences, Kyungpook National University, Daegu, South Korea; 3Department of Pharmaceutical Engineering, Dankook University, Cheonan, South Korea; 4Department of Pharmaceutical Engineering, Gyeongnam National University of Science and Technology, Jinju, South Korea*These authors contributed equally to this workPurpose: The objective of this study was to exploit a novel methotrexate (MTX)-loaded solid self-microemulsifying drug delivery system (SMEDDS) with enhanced bioavailability and photostability.Materials and methods: The optimized liquid SMEDDS was composed of castor oil, Tween® 80, and Plurol® diisostearique at a voluminous ratio of 27:63:10. The solid SMEDDS was formulated by spray drying liquid SMEDDS with the solid carrier (calcium silicate). Particle size analyzer, scanning electron microscopy (SEM), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and Fourier transform infrared (FTIR) spectroscopy experiments characterized the physiochemical properties of the MTX-loaded solid SMEDDS. These properties include a z-average diameter of emulsion around 127 nm and the amorphous form of the solid SMEDDS. Furthermore, their solubility, dissolution, and pharmacokinetics in Sprague-Dawley rats were analyzed in comparison with the MTX powder.Results: The final dissolution rate and required time for complete release of solid SMEDDS were 1.9-fold higher and 10 min shorter, respectively, than those of MTX powder. Pharmacokinetic analysis demonstrated 2.04- and 3.41-fold increments in AUC and Cmax, respectively in comparison to MTX powder. The AUC and Cmax were significantly increased in solid SMEDDS. Finally, the photostability studies revealed the substantially enhanced photostability of the MTX-loaded SMEDDS under the forced degradation and confirmatory conditions.Conclusion: This solid SMEDDS formulation could be an outstanding candidate for improving the oral bioavailability and photostability of MTX.Keywords: methotrexate, solid SMEDDS, solubility, bioavailability, photostability